Implementasi Aplikasi Simatrik Oleh Diskominfotiks Rokan Hilir Dalam Pengelolaan kerja Sama Media Pemerintah Daerah - Sabili Al Qodri; Yantos (Al-Manar Journal of Public Administration and Management, 2026)
Digital transformation in public services, particularly in managing media collaboration between local governments and the mass media, is underway. The Rokan Hilir Regency Communications, Informatics, Statistics, and Cryptography Service (Diskominfotiks) developed the Media Partnership Management Information System (SIMATRIK) application as a digital-based innovation to improve efficiency, transparency, and accountability in media collaboration processes. However, its implementation still faces various obstacles, such as limited human resources, low digital literacy, and technical and infrastructure constraints. This study aims to understand an analyze the implemention of the SIMATRIK application and identify the obstacles encountered. This study used a qualitative method with a descriptive approach. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis was conducted systematically to understand the implementation process based on George C. Edward III’s policy implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The research results are expected to provide an in-depth overview of the implementation of the SIMATRIK application in supporting the digitalization of regional governmrnt media collaboration and serve as evaluation material for the Communication and Information Technology Office (Diskominfotiks) in improving the effectiviness of its systems and the quality of information technology-based public services.